Análisis de la pintura La profecía de la vida de San Francisco de Asís. Museo Colonial de San Francisco (Chile) - Rojas Gamarra, Walter Toribio (2023)
The series of the life of San Francisco de Asís in Santiago de Chile was requested to Cuzco in the seventeenth century, to the workshops of Basilio de Santa Cruz and Diego Quispe Tito. It has a counterpart in the city of Cusco (40 canvases) and is developed in the style of the baroque school. The Franciscan Bishop Fray Diego Humanzoro makes the order. We will analyze the first painting of the series (1/53) entitled The prophecy. Francisco appears with wings, already showing the stigmata, as if he were an angel, the spiritual heritage, which arises from the millenarian movement whose advocate is the Abbot Joaquin de Fiore, who will prophesy a new apostolic era, he era of the Holy Spirit, which would completely transform the Church with the advent of two mendicant orders, the Franciscans and the Dominicans. From the first would emerge Il poverello di Assisi.